Circulating Discourses of Minority Education: The Linguistic Construction of Modernity in Globalizing Taiwan. (March 2015) - Lin, Shumin
<x xml:space="preserve">Abstract</x> Drawing on 15 months of fieldwork in Taiwan, this article analyzes circulating discourses and practices across heterogeneous scales that conflate Taiwanese minority‐language elders with foreign brides as nonmodern and childlike. The assiduous production and reproduction of historically and geographically displaced linguistic Others is part and parcel of the production of Taiwan's modern 21st‐century identity. Through this construction of the linguistic Other, Taiwan asserts itself as an already modern society.